2015
DOI: 10.1074/jbc.m115.637488
|View full text |Cite
|
Sign up to set email alerts
|

Soluble Urokinase Receptor Is Released Selectively by Glioblastoma Cells That Express Epidermal Growth Factor Receptor Variant III and Promotes Tumor Cell Migration and Invasion*

Abstract: Background:In glioblastoma, the EGF receptor mutation, EGFRvIII, is a biomarker of tumor aggressiveness even when only a small subpopulation of the cells express EGFRvIII. Results: EGFRvIII-expressing cells release soluble uPAR (suPAR), which activates cell signaling and promotes migration and invasion of EGFRvIII-negative cells. Conclusion: suPAR functions as a paracrine cancer-promoting factor in glioblastoma. Significance: suPAR is biologically active and may contribute to cancer aggressiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
1
13
0
Order By: Relevance
“…The malignant potential of human meningiomas and gliomas has been correlated with uPAR expression, which parallels our finding of significantly increased uPAR expression in canine high-grade gliomas compared with other tumor types and grades 1,8,13…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…The malignant potential of human meningiomas and gliomas has been correlated with uPAR expression, which parallels our finding of significantly increased uPAR expression in canine high-grade gliomas compared with other tumor types and grades 1,8,13…”
Section: Discussionsupporting
confidence: 86%
“…Similarities in the clinical behavior, morphology, molecular signatures, and genetic aberrations have been observed between human and canine brain tumors, which has resulted in the emergence of the brain tumor bearing dog as a model for translational research 9,10,24. While these tumors represent a phenotypically, clinically, and genomically heterogeneous group of cancers, a shared pathophysiological denominator that contributes to the challenges associated with their treatment is their ability to invade the brain parenchyma 8. In this study, using several complementary methods, we have demonstrated that uPAR protein and mRNA are overexpressed and uPA activity is present in the most commonly encountered canine primary brain tumors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interaction between PLAUR and EGFR was previously studied. Glioblastoma cells expressing EGFR variant III release soluble PLAUR, which promotes cell migration and invasion [55], while PLAUR induces EGFR transactivation in MCF-7 cells [56] and T-HEp3 cells [15]. Although previous studies have demonstrated that PLAUR inhibits EGFR tyrosine kinase activity, those reports did not show the expression of EGFR regulated by PLAUR.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 39%
“…During development uPA-uPAR binding promotes neuritogenesis and neuronal migration via a combination of proteolytic and non-proteolytic mechanisms [17,18] . More specifically, during the early stages of development uPAR regulates the reorganization of the cytoskeleton in post-mitotic neurons via activation of integrins and the focal kinase adhesion (FAK) pathway [17] , thus promoting axonal growth, and neuronal migration [19] and branching [20] . Interestingly, it has also been reported that uPAR participates in the formation of those neuronal circuits that underlie language and cognition, and that dysregulation of the uPA-uPAR signaling pathway is related with the development of epilepsy [21] .…”
Section: Upa-upar Expression In the Central Nervous Systemmentioning
confidence: 99%